Rancang Bangun Aplikasi Android Untuk Monitoring Pasokan Bawang Merah Di Kabupaten Enrekang - Ahsan Mubarak; Marlina Marlina; Hasnawati Hasnawati (Jurnal Ilmiah Sistem Informasi dan Teknik Informatika (JISTI), 2025)
Enrekang Regency plays a crucial role as a primary producer of shallots in South Sulawesi, contributing significantly to regional supply. Despite its importance, supply monitoring still carried out using conventional methods, often resulting in inaccurate records, delayed distribution, and unstable pricing. This study focuses on developing a mobile-based application to enable efficient, real-time monitoring of shallot stock. The research adopts an R&D approach through a prototyping methodology, with data collected from interviews and literature reviews. System modeling was conducted incorporating various UML tools—such as use case, activity, and sequence diagrams. The application was constructed in Android Studio, adopting Kotlin as its core language and relying on MySQL for database operations. The framework is capable of documenting, tracking, and managing inventory data. Core features include user registration, kiosk management, product entry, and transaction simulations. Functionality testing applied black-box and white-box techniques to ensure the system behaved as expected. Ultimately, this application aims to deliver accessible and accurate data to farmers, sellers, and local government, fostering more effective supply chain management and price stability in the Enrekang region.